2016
DOI: 10.1021/acsami.5b12125
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescence Properties of Novel Ce3+- and Eu2+-Doped Lanthanum Bromothiosilicate La3Br(SiS4)2 Phosphors for White LEDs

Abstract: Novel Ce(3+)- and Eu(2+)-doped lanthanum bromothiosilicate La3Br(SiS4)2:Ce(3+)and La3Br(SiS4)2:Eu(2+) phosphors were prepared by solid-state reaction in an evacuated and sealed quartz glass ampule. The La3Br(SiS4)2:Ce(3+) phosphor generates a cyan emission upon excitation at 375 nm, whereas the La3Br(SiS4)2:Eu(2+) phosphor could be excited with extremely broad range from UV to blue region (300 to 600 nm) and generates a reddish-orange broadband emission centered at 640 nm. In addition, thermal luminescence pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…1,2 The eld of solid state lighting applications like phosphor converted WLEDs is in need of new thermally and chemically stable high quantum yield red phosphors which absorb UV and visible radiations for producing white light of appropriate color rendering index (CRI) and correlated color temperature (CCT). 3 The Eu 3+ ion is an essential activator for many inorganic lattices to produce orange-red emission by the transitions 5 D 0 / 7 F J , J ¼ 0, 1, 2, 3. 4 Eu 3+ can also be used as a structural probe since its absorption and emission spectrum depends on its site symmetry in the host lattice.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The eld of solid state lighting applications like phosphor converted WLEDs is in need of new thermally and chemically stable high quantum yield red phosphors which absorb UV and visible radiations for producing white light of appropriate color rendering index (CRI) and correlated color temperature (CCT). 3 The Eu 3+ ion is an essential activator for many inorganic lattices to produce orange-red emission by the transitions 5 D 0 / 7 F J , J ¼ 0, 1, 2, 3. 4 Eu 3+ can also be used as a structural probe since its absorption and emission spectrum depends on its site symmetry in the host lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The nal prole Rfactors, R wp , R p , and c 2 obtained were 8.62%, 6.19% and 1.539, respectively, which suggested that the pure NaCaPO 4 :0.01Eu 2+ with 0.03NaCl was successfully synthesized. NaCaPO 4 was indexed to an orthorhombic crystal system and space group Pnam (a ¼ 0.6797 nm, b ¼ 0.9165 nm, c ¼ 0.5406 nm, and V ¼ 0.3368 nm 3 ). The cell parameters and volume of NaCaPO 4 :0.01Eu 2+ with 0.03NaCl were a ¼ 0.680 nm, b ¼ 0.916 nm, c ¼ 0.542 nm, and V ¼ 0.3376 nm 3 , which are larger than those of NaCaPO 4 , indicating that Eu 2+ was doped into the host.…”
Section: Resultsmentioning
confidence: 99%
“…NaCaPO 4 was indexed to an orthorhombic crystal system and space group Pnam (a ¼ 0.6797 nm, b ¼ 0.9165 nm, c ¼ 0.5406 nm, and V ¼ 0.3368 nm 3 ). The cell parameters and volume of NaCaPO 4 :0.01Eu 2+ with 0.03NaCl were a ¼ 0.680 nm, b ¼ 0.916 nm, c ¼ 0.542 nm, and V ¼ 0.3376 nm 3 , which are larger than those of NaCaPO 4 , indicating that Eu 2+ was doped into the host. The crystal structure of NaCaPO 4 viewed down the b-axis and the coordination polyhedron was composed of a Na/Ca/P atomic site, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the traditional light source, it has the advantages of high brightness, environmental friendliness, long duration, and energy saving. [ 2 ] Nowadays, the universal method for obtaining white light is to combine a Y 3 Al 5 O 12 :Ce 3+ (YAG:Ce 3+ ) yellow phosphor with an InGaN blue LED chip. [ 3 ] Meanwhile, this approach suffers from poor color‐rendering ( R a < 75) and high correlated color temperatures (CCT > 4500 K) due to the lack of a red spectral component.…”
Section: Introductionmentioning
confidence: 99%